Immobilized Ru(II) catalysts for transfer hydrogenation and oxidative alkene cleavage reactions - Kotze, Hendrik de Vries (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.